1997
DOI: 10.1007/bf02460845
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 17 Paracoccidioides brasiliensis isolates

Abstract: We have studied the physiological and morphological features of 17 isolates of Paracoccidioides brasiliensis in order to define their phenotypes. The isolates were cultured at room temperature on potato dextrose agar (PDA, Difco) slants for mycelial growth and in 1% dextrose brain heart infusion agar (BHIA, Difco) at 37~ for the study of yeast forms. Most mycelial and yeast forms grew well between pH 5.6-9.4. In their response to osmotic pressure the isolates were separated in three groups: intolerant, interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
4
12
0
Order By: Relevance
“…We found a similar result with all those isolates of S. schenckii. In a similar study, with isolates of Paracoccidiodes brasiliensis, Sano et al found that mycelial forms rather than yeast forms could split urea [22]. In the present study, 91.8% of the isolates could tolerate a maximum of 7% salt concentration in their mycelial form whereas 24% of yeast forms tolerated a salt concentration of up to 11%.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…We found a similar result with all those isolates of S. schenckii. In a similar study, with isolates of Paracoccidiodes brasiliensis, Sano et al found that mycelial forms rather than yeast forms could split urea [22]. In the present study, 91.8% of the isolates could tolerate a maximum of 7% salt concentration in their mycelial form whereas 24% of yeast forms tolerated a salt concentration of up to 11%.…”
Section: Discussionsupporting
confidence: 69%
“…There is no study available to compare the pH and osmotolerance of S. schenckii strains. However, in the report of Sano et al a majority of P. brasiliensis strains grew well between pH 5.6 and 9.4 and but had variable osmotolerance [22].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This leads to a detectable mutant phenotype characterized by reduced growth, roundcell morphologies, sensitivity to CW, increased cell wall permeability and secretion (Popolo & Vai, 1999;Vai et al, 2000). In fact, yeast forms did not grow below pH 3.6; most of the clinical isolate strains require a pH of culture medium above 5.6 and the establishment of yeast infection takes place in host tissues at pH values close to neutrality (Franco, 1986;Sano et al, 1997;Restrepo et al, 2001). Similar results were found for GAS4 of S. cerevisiae, a paralogue of GAS1, encoding a protein specialized to function at a pH value close to neutrality (Ragni et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…This requirement could reflect both the environmental growth conditions of P. brasiliensis and the pH of the niches colonized by this dimorphic pathogen. In fact, yeast forms did not grow below pH 3.6; most of the clinical isolate strains require a pH of culture medium above 5.6 and the establishment of yeast infection takes place in host tissues at pH values close to neutrality (Franco, 1986;Sano et al, 1997;Restrepo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%